PERANCANGAN AGROWISATA KECAMATAN MOADAYAG DENGAN PENDEKATAN ARSITEKTUR EKOLOAGI - Yusnan Mokoagow; Zuhriati A. Djailani; Ernawati Ernawati (JAMBURA Journal of Architecture, 2023)
ABSTRACT.In accordance with the vision "The Realization of Modayag Regency which is Independent in Staple Foods" with several missions related to improving the quality of human resources and being able to trigger growth in socio-economic development, as well as increasing economic business in the agricultural sector. By Tourism Law no. December 2009, a tourist destination is anything that has uniqueness, beauty and natural, cultural and man-made wealth which is the object or destination of tourist visits. The main problem in this design is the geographical and climatic conditions in the adjustment of plant species with the arrangement of agro-tourism areas. The ecological architectural approach aims to minimize the impact of natural damage by integrating with the environment. The method used in this research is descriptive quantitative. The implementation technique is by conducting a site survey and collecting primary and secondary data which is analyzed descriptively. Then the management of primary data and secondary data will become an alternative solution to the problem and become a reference for agro-tourism design concepts. Data that includes design requirements are processed into analysis. This analysis becomes a reference for the concept of agro-tourism planning. By prioritizing ecological aspects so as to use bamboo and wood as the main materials in the designer, as well as maximizing natural lighting, ventilation in each room and outdoor space arrangement taking into account user comfort.Keywords: agrotourism, ecology, designABSTRAK.Sesuai dengan visi “Terwujudnya Kecamatan Modayag Yang Mandiri Pangan Pokok" dengan beberapa misi diantaranya terkait peningkatan kualitas sumber daya manusia dan dapat memicu pertumbuhan pembangunan sosial ekonomi, serta meningkatkan usaha ekonomi dalam sektor hasil pertanian. Dengan Undang-undang Kepariwisataan No. Desember 2009, destinasi wisata adalah segala sesuatu yang memiliki keunikan, keindahan dan kekayaan alam, budaya, dan buatan manusia yang menjadi obyek atau tujuan kunjungan wisata. Permasalahan utama dalam perancanagn ini adalah keadaan geografis dan iklim dalam penyesuaian untuk jenis tanaman hingga pada penataan kawasan agrowisata. Pendekatn arsitektur ekologi bertujuan untuk meminimalisir terkait dampak kerusakan alam dengan cara berintegrasi dengan lingkungan. Metode yang digunakan dalam penelitian adalah deskriptif kuantitatif. Teknis pelaksanaanya dengan melakukan survei lokasi dan melakukan pengumpulan data primer dan sekunder yang dianalisis secara deskriptif. Kemudian, mengelola data primer dan data sekunder akan menjadi alternatif pemecahan masalah dan menjadi acuan konsep perancangan agrowisata. Data-data yang mencakup kebutuhan perancangan di olah menjadi analisis. Analisis tersebut menjadi acuan konsep perencanaan agrowisata. Dengan mengedepankan aspek ekologi sehingga mengunakan bambu dan kayu sebagia material utama dalam perancang, serta memaksimalkan pencahayaan alam, penghawaan pada setiap ruangan dan penataan pada ruang luar untuk mempertimbangkan kenyamanan pengguna.Kata kunci: agrowisata, ekologi, perancangan